Circadian fluctuations in circulating plasminogen activator inhibitor-1 are independent of feeding cycles in mice. (7th February 2017) - Oishi, Katsutaka; Ohkura, Naoki; Yasumoto, Yuki; Yamamoto, Saori
ABSTRACT: To evaluate the involvement of the day-night feeding cycle in the circadian regulation of circulating plasminogen activator inhibitor-1 (PAI-1) concentrations, mice were fed with a diet for eight hours during either daytime (DF) or nighttime (NF) for one week. The reversed feeding cycle did not affect the circadian phases of plasma PAI-1 levels as well as the nocturnal wheel-running activity, although the phase of Pai-1 mRNA expression was significantly advanced for 8.6 hours in the livers of DF, compared with NF mice. The day-night feeding cycle is not a critical Zeitgeber for circadian rhythm of circulating PAI-1.